Development of Soccer Passing, Dribbling, Shooting Technique Skill Instruments - Agus Santosa; Rifal Firdaus (UNIB Press, 2024)
This study aims to produce shortpass, longpass, dribbling and shooting instrument/measurement products in soccer skills. This type of research is ADDIE development research (Analysis, Design, Development, Evaluation). This research was conducted through the stages: 1) analysis, 2) design, 3) implementation, 4) evaluation. The population used in this study were all STKIP Pasundan Cimahi soccer UKM students, and for sampling using a purposive sampling technique, namely 10 STKIP Pasundan Cimahi students who had played in league 3. Data analysis techniques used descriptive in the form of scores and time converted in percentage form. The results showed that the instrument/measuring shortpass got a maximum score of 11 with a percentage of 0.91 included in the high category. The long pass instrument, getting a maximum score with a presentation of 0.91 is included in the high category, the development of the dribbling instrument getting a maximum score of 11 with a presentation of 0.91 is included in the high category. The shooting development instrument gets a score with a percentage of 0.91 which is included in the high category. Conclusion So in this study is a soccer skills development instrument that can be used properly.